The Relationship Between Coping Mechanisms And Stress Levels In Nursing Students During Clinical Practice - Nurnainah Nurnainah; Abdurrahman Abdurrahman; Abu Bakar Betan (International Journal of Health Sciences, 2025)
Background: The clinical practice period is a crucial stage in nursing education, aimed at developing students' professional competence. However, this phase is often a source of stress due to academic demands, clinical responsibilities, and the pressures of the hospital environment. Poorly managed stress can reduce students' performance, motivation, and mental health. One factor influencing stress levels is coping mechanisms, namely how individuals deal with psychological pressure. Objective: This study aims to analyze the relationship between coping mechanisms and stress levels in nursing students during clinical practice at a teaching hospital. Method: This study used a correlational analytical design with a cross-sectional approach. The study population was all final-year nursing students who were practicing clinically at Hospital X, totaling 100 people, with a sample of 80 respondents selected using purposive sampling. The instrument used was the Perceived Nursing Questionnaire. Stress Scale (PSS) to measure stress levels and Coping Orientation to Problems Experienced (COPE Inventory) to assess coping mechanisms. Data were analyzed using the Spearman test. Rank to find out the relationship between variables. Results: Most students used adaptive coping mechanisms (72.5%) and experienced moderate stress levels (65%). The analysis showed a significant negative relationship between coping mechanisms and stress levels (p = 0.001; r = -0.512). This means that the more adaptive the coping mechanisms used, the lower the students' stress levels during clinical practice. Conclusion: There is a significant relationship between coping mechanisms and stress levels in nursing students. Adaptive coping mechanisms have been shown to play a significant role in reducing stress during clinical practice. Support from educational institutions through stress management training programs and psychological counseling is needed to enable students to effectively cope with academic and work pressures.